When serology fails: recognising systemic lupus erythematosus in the absence of autoantibodies - Khawla K. Alghanim; Shoq O. Alshammari; Hanan T. Albaqshi (European Journal of Case Reports in Internal Medicine, 2025)
The diagnosis of systemic lupus erythematosus (SLE) typically relies on characteristic autoantibodies and standardised classification criteria, and these serological markers guide both diagnosis and treatment decisions. But in rare cases, patients present with seronegative disease, creating significant diagnostic challenges that can delay appropriate intervention. Therefore, we present a case demonstrating the importance of clinical vigilance and histopathological confirmation in seronegative SLE. A 43-year-old woman with hypothyroidism developed inflammatory polyarthritis with consistently negative autoimmune serologies – rheumatoid factor, anti-cyclic citrullinated peptide antibodies, antinuclear antibodies, and anti–double-stranded deoxyribonucleic acid antibodies – despite elevated inflammatory markers. Initial treatment with hydroxychloroquine and corticosteroids elicited a significant therapeutic response. After 5 years, she developed a rapid decline in renal function with nephritic-range proteinuria. Renal biopsy revealed crescentic immune-complex glomerulonephritis with IgG, IgM, C3, and C1q deposits, confirming lupus nephritis. Aggressive therapy with intravenous methylprednisolone, plasma exchange, and cyclophosphamide, followed by maintenance therapy with mycophenolate mofetil, hydroxychloroquine, and oral corticosteroids, achieved clinical improvement and renal stabilisation. This case demonstrates that negative serologies should not preclude a diagnosis of SLE when the clinical presentation suggests systemic autoimmunity. Early renal biopsy and aggressive immunosuppression can prevent irreversible organ damage in seronegative disease. These findings support recognising seronegative SLE as a distinct disease subset and advocate for more inclusive diagnostic approaches beyond serological testing.